Analytical modeling of a time-threshold based multi-guard bandwidth allocation scheme for cellular networks - Candan, Idil; Salamah, Muhammed (IEEE, 2009)
In this paper, the analytical modeling of a time-threshold based multi-guard bandwidth allocation scheme is presented using a two-dimensional markov chain. The main idea of the scheme is based on monitoring the elapsed real time of handoff calls and according to a time threshold (t(e)), a handoff call is either slightly-prioritized or fully-prioritized. A slightly-prioritized handoff call has higher priority than a new call and lower priority than a fully-prioritized handoff call. Also in this paper, the numerical results obtained from two dimensional markov chain analysis are compared with the numerical results which are obtained using one-dimensional markov chain analysis and simulation ones. The simulation and analytical results agree well. The performances of different bandwidth allocation schemes are measured using a crucial general performance metric Z. Z, which is a performance/cost ratio, is a function of the new call blocking probability, handoff call dropping probability and system utilization all together. The results indicate that our scheme outperforms other traditional schemes.
5th Advanced International Conference on Telecommunications -- MAY 24-28, 2009 -- Venice, ITALY
Keywords: Analytical model; handoff; markov process; cellular networks